2021
DOI: 10.1007/s11242-021-01598-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas Trapping on Foam Mobility in a Model Fracture

Abstract: In enhanced oil recovery, foam can effectively mitigate conformance problems and maintain a stable displacement front, by trapping gas and reducing its relative permeability in situ. In this study, to understand gas trapping in fractures and how it affects foam behavior, we report foam experiments in a 1-m-long glass model fracture with a hydraulic aperture of 80 $$\upmu $$ μ m. One wall of the fracture is rough, and the other is smooth. Between the two is a 2D porous medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…They observed noticeable foam trapping in fractures with apertures of less than 50 μm. Li and Rossen 32 confirmed that by increasing the interstitial velocity and pressure gradient, gas trapping decreased and foam texture becomes finer. In rough-walled fractures, foam propagation through permeable paths produces strong flow resistance.…”
Section: Foam In Fracturesmentioning
confidence: 92%
See 1 more Smart Citation
“…They observed noticeable foam trapping in fractures with apertures of less than 50 μm. Li and Rossen 32 confirmed that by increasing the interstitial velocity and pressure gradient, gas trapping decreased and foam texture becomes finer. In rough-walled fractures, foam propagation through permeable paths produces strong flow resistance.…”
Section: Foam In Fracturesmentioning
confidence: 92%
“…Microscale observations using silicon-based micromodels are extensive for studying multiphase flow properties and fluid–fluid interactions. 19,32,36,37 An instrumented micromodel is useful to visualize the microscopic flow of foam in fractures. This instrument enables pressure drop measurements and foam microstructure observations for a wide range of flow rates and foam qualities.…”
Section: Methodsmentioning
confidence: 99%
“…Foam is further refined as it propagates through the model fracture due to in-situ bubble generation, mainly by lamella division [26]. After foam achieves steady-state, bubble generation and destruction rates are in local equilibrium in the second half of the model fracture [26]. In this study, the designed velocities ensure that foam reaches a stable pressure gradient, and they are not great enough to compromise the safety of our setup with glass model fractures.…”
Section: Coarsening Experiments and Image Analysismentioning
confidence: 98%
“…Li et al diffusion between the mixing tee and the inlet of the fracture, the pregeneration step ensures that gas enters the fracture as relatively large bubbles instead of elongated gas slugs. Foam is further refined as it propagates through the model fracture due to in-situ bubble generation, mainly by lamella division [26]. After foam achieves steady-state, bubble generation and destruction rates are in local equilibrium in the second half of the model fracture [26].…”
Section: Coarsening Experiments and Image Analysismentioning
confidence: 99%